Choroid plexus papilloma in a free ranging eared dove (Zenaida auriculata) - Navas-Suárez, Pedro Enrique; Ervedosa, Ticiana Brasil; di Loreto, Celso; Ressio, Rodrigo Albergaria; Jesus, Isis Paixão de; Silva, Mariana Morgado Hereny da; Frediani, Mayra Hespanhol; Guerra, Juliana Mariotti; Fernandes, Natália C.C. de A. (Brazilian Journal of Veterinary Pathology, 2021)
Choroid plexus tumors (CPT) are rare neoplasms and histologically classified as choroid plexus papilloma (CPP), atypical choroid plexus papilloma (APP), and choroid plexus carcinoma (CPC). These neoplasms have been described in humans, domestic animals (canine, feline, equine, caprine) and some wild animals (cetaceans and Psittacidae birds). To our best knowledge, herein we report the first CCP in a free-ranging eared dove (Columbiformes; Zenaida auriculata, de Murs 1847). Histologically, the ventricle was dilated, with a papillary proliferation (arboriform pattern) in topography of CP. The neoplasm was well-differentiated, composed by a single layer of cuboidal cells, anchored in a delicate fibrovascular stroma. The neoplastic cells exhibited moderate stroma, with well-defined borders and round nuclei, with vesicular chromatin and inconspicuous nucleoli. Mitotic activity was low (